2004
DOI: 10.1080/10408440490464705
|View full text |Cite
|
Sign up to set email alerts
|

The Toxicology of Perfluorooctanoate

Abstract: PFOA is a peroxisome proliferator (PPAR agonist) and exerts morphological and biochemical effects characteristic of PPAR agonists. These effects include increased beta-oxidation of fatty acids, increases in several cytochrome P-450 (CYP450)-mediated reactions, and inhibition of the secretion of very low-density lipoproteins and cholesterol from the liver. These effects on lipid metabolism and transport result in a reduction of cholesterol and triglycerides in serum and an accumulation of lipids in the liver. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
422
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 681 publications
(445 citation statements)
references
References 115 publications
16
422
1
2
Order By: Relevance
“…Perfluoro-octanoic acid (PFOA), a large, anionic fluorocarbon, is unlike any of the other anions. This, along with recent research interest in this compound as an environmental contaminant, makes it a good choice for inclusion in this study [25,26].…”
Section: Methodsmentioning
confidence: 99%
“…Perfluoro-octanoic acid (PFOA), a large, anionic fluorocarbon, is unlike any of the other anions. This, along with recent research interest in this compound as an environmental contaminant, makes it a good choice for inclusion in this study [25,26].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to their hormonal effects, animal studies have demonstrated developmental toxicity, reproductive toxicity, hepatotoxicity, neurotoxicity, immunotoxicity and tumorigenicity of the perfluorinated compounds (Johansson et al, 2008;Kennedy et al, 2004;Lau et al, 2004). Hepatocellular adenomas, testicular Leydig cell adenomas and pancreatic acinar cell adenomas have been reported in rats after exposure to PFOA in the diet for 2 years (Biegel et al, 2001;Butenhoff et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…In one of the aforementioned analyses, Olsen et al (2003a) reported a positive association between PFOA and serum cholesterol and triglycerides among participants of a fluorochemical medical surveillance program conducted in 2000 at the 3M Antwerp and Decatur facilities. They considered this a spurious finding given the toxicological evidence in mice and rats that shows PFOA, a peroxisome proliferator alpha receptor agonist (PPARa), exerts effects including increased beta-oxidation of fatty acids, inhibition of the secretion of very low-density lipoproteins and cholesterol from the liver, and a reduction of cholesterol and triglycerides in serum and accumulation of lipids in the liver (Maloney and Waxman 1999;Xie et al 2003;Kennedy et al 2004). No associations were reported between PFOA and either serum cholesterol or triglycerides for the Cottage Grove male employees who participated in the same fluorochemical medical surveillance program in 2000 (Olsen et al 2003c).…”
Section: Introductionmentioning
confidence: 99%